KELANGSUNGAN DAN PERUBAHAN INDIVIDUALISME AMERIKA: KAJIAN TEKSTUAL DAN KONTEKSTUAL TERHADAP PIDATO PELANTIKAN PRESIDEN FRANKLIN DELANO ROOSEVELT - Eko Rujito DA (Sunan Kalijaga State Islamic University Yogyakarta, 2010)
This study examines Franklin Delano Roosevelt's four inaugural addresses to find out the continuity and change of American traditional value, namely individualism. This study is purely a library research based on textual interpretation of those inaugural addresses in revealing any continuity and change of American traditional value mentioned above. Applying an interdisciplinary andholistic approach, the writer attempts to analyze the continuity and change of American individualism values found in those inaugural addresses in the socio-cultural, historical and biographical contexts. This study begins with introductory notes, and then goes on to a discussion of the origins and significance of American individualism. The next part is a discussion on the continuity and change of American individualism found in those inaugural addresses, both textually and contextually. The study finds that there are continuity and change in the interpretation of American individualism expressed in those inaugural addresses. These continuity and change are inevitable the result of the dynamic in economy, politic, and socio-cultural in America during the thirties and early forties.